Analysis of the notifications of adverse drug events in a Brazilian public hospital - Larissa Duarte SANTOS; Helena Márcia MORAES; Cassia Lima FERREIRA; Gabriela Guimarães RODRIGUES; Mariana Gonzaga NASCIMENTO; Caryne Margotto BERTOLLO (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective: to describe the adverse drug events (ADE) reported to the Brazilian Health Regulatory Agency (Anvisa) by a public hospital of the Sentinel Network in Belo Horizonte. Method: descriptive observational study, with analysis of the complete ADE notifications registered at VigiMed by the Permanent Committee for Hospital Sanitary Risk Management from January 2021 to May 2022. The notified ADEs were described according to their distribution by month, by sector and according to their classification as adverse drug reaction (ADR) or medication error. The drugs involved in the notifications were classified according to the first level of the Anatomical Therapeutic Chemical (ATC) code from World Health Organization. Results: 74 notifications were analyzed, with a median of five notifications each month. Of those, 14 (18.9%) were ADR; seven (9.4%) were prescription errors; 11 (14.9%) were dispensing errors and 42 (56.8%) were administration errors. The sectors with the highest number of notifications were adult ward - inpatient, oncology - outpatient and pharmacy units. The class of drugs most involved in ADE was “Blood and Blood-forming Organs” (20.3%), followed by “Anti-infectives for systemic use” (18.9%). Conclusion: In this study, the ADEs notified to Anvisa at a public hospital of the Sentinel Network of Belo Horizonte were described qualitatively and quantitatively. Most of the ADEs were drug administration errors and there was a reduced number of ADR notifications. The analysis of these notifications can help the institution with the implementation of preventive and corrective measures to improve the safety in the prescription, use and administration of medicines. It is important to encourage the notification culture to better understand the profile of errors related to the drug chain and act effectively to reduce them.